2006
DOI: 10.1038/sj.jid.5700034
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Testing for Oculocutaneous Albinism Type 1 and 2 and Hermansky–Pudlak Syndrome Type 1 and 3 Mutations in Puerto Rico

Abstract: Hermansky-Pudlak syndrome (HPS) (MIM #203300) is a heterogeneous group of autosomal recessive disorders characterized by oculocutaneous albinism (OCA), bleeding tendency, and lysosomal dysfunction. HPS is very common in Puerto Rico (PR), particularly in the northwest part of the island, with a frequency of approximately 1:1,800. Two HPS genes and mutations have been identified in PR, a 16-base pair (bp) duplication in HPS1 and a 3,904-bp deletion in HPS3. In Puerto Ricans with more typical OCA, the most common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 20 publications
2
36
1
Order By: Relevance
“…Type 1 HPS occurs with a frequency of one in 1,800 in northwest Puerto Rico due to a founder effect 12 and it has a carrier frequency of 1:21 8 . Torres and co-workers 24 found that type 3 HPS has an average carrier frequency of 1:85 among Puerto Rican newborns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Type 1 HPS occurs with a frequency of one in 1,800 in northwest Puerto Rico due to a founder effect 12 and it has a carrier frequency of 1:21 8 . Torres and co-workers 24 found that type 3 HPS has an average carrier frequency of 1:85 among Puerto Rican newborns.…”
Section: Discussionmentioning
confidence: 99%
“…6–7 HPS is thought to be the most common single-gene disorder in Puerto Rico (PR) where it has been reported to occur 1:1,800. 6,8 Type 1 HPS is the more prevalent in the above mentioned island and have been found to be more common in the northwestern part of it, in contrast to the type 3 HPS which is more common in the central area.…”
Section: Introductionmentioning
confidence: 93%
“…In northwest Puerto Rico, 1 in 21 persons is a carrier of the founder mutation (16bp duplication in exon 15 of HPS1 8 ) and 1 in 1800 persons suffers from HPS-1 9 . Due to another founder mutation (3,904bp deletion in HPS3 ), one in 4000 people in central Puerto Rico is affected with HPS-3 10,11 . Multiple other HPS1 mutations have been identified and HPS-1 is also the most common subtype of HPS in non-Puerto Ricans (25%) 1 .…”
Section: Epidemiologymentioning
confidence: 99%
“…Most patients are found in central Puerto Rico, due to a 3,904-bp deletion in the HPS3 gene [6]. Other mutations in the HPS3 gene have been reported in non-Puerto Rican patients.…”
mentioning
confidence: 99%
“…The pulmonary tract is affected only mildly or not at all, with slight reductions in forced vital capacity (FVC) [3]. Granulomatous colitis has been described in only two patients with HPS-3 [6]. Only a few patients with HPS-5, HPS-6, HPS-7 and HPS-8 have been diagnosed worldwide.…”
mentioning
confidence: 99%